Implementation Discovery Learning Model on the Learning Outcomes of Football Passing - M Haris Satria; Andreas Guruh Susanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This research aims to determine the implementation of the discovery learning model on the learning outcomes of class X.4 football passing at SMA Az-Zahrah Palembang. The discovery learning model facilitates students to critical thinking, increase their activeness, understanding and learning experience with direct involvement in the learning process so that they can conclude for themselves the meaning of learning. This research aims to see whether the discovery learning model can improve students' football passing learning outcomes in the physical education learning process. This research is classroom action research. The research subjects were 27 class X.4 students. This research was carried out collaboratively between researchers and teachers. This research was carried out in 2 cycles (planning, implementation, evaluation and reflection). Data collection by observation and documentation. The results of the research show the ability to increase learning outcomes in football passing using the discovery learning model. This can be seen from the results of the pre-action completeness percentage of 55.56% to 85.18% in cycle I and to 100% completeness in cycle II. The discovery learning model can be implemented to improve learning outcomes of football passing.